1944
DOI: 10.1085/jgp.27.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Anomalous Viscosity and Flow-Birefringence of Protein Solutions

Abstract: 1. An investigation of the physicochemical properties of myosin has been carried out. Prepared under standard conditions, the ratio of flow-birefringence to protein concentration is uniform. The effect of electrolytes, pH, and urea on the flow-birefringence and viscosity (relative and anomalous) of myosin has been examined. 2. Decrease or abolition of flow-birefringence does not necessarily imply far reaching denaturation, since such effects can be reversed by a variety of means. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

1944
1944
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(8 citation statements)
references
References 7 publications
1
6
1
Order By: Relevance
“…This limitation in the behavior of Engelhardt's fiber may be due to the operations required to extract myosin and form it into threads. Our assumption is, furthermore, in direct contradiction to the view of the Needham group's work (Dainty et al, 1944), which led to the inference that contracting myosin is represented by the M,-ATP combination. This work, however, was performed on myosin rnicellae in solution, and, as the Needham paper states, "It must be remembered that, in vitro, the contraction of the myosin particles does no work, and the conditions are therefore very different from those in vi'uo.''…”
Section: A Theory Of Mechano-chemical Couplingcontrasting
confidence: 83%
“…This limitation in the behavior of Engelhardt's fiber may be due to the operations required to extract myosin and form it into threads. Our assumption is, furthermore, in direct contradiction to the view of the Needham group's work (Dainty et al, 1944), which led to the inference that contracting myosin is represented by the M,-ATP combination. This work, however, was performed on myosin rnicellae in solution, and, as the Needham paper states, "It must be remembered that, in vitro, the contraction of the myosin particles does no work, and the conditions are therefore very different from those in vi'uo.''…”
Section: A Theory Of Mechano-chemical Couplingcontrasting
confidence: 83%
“…In the 1930s, studies of myosin revealed its elongated shape [] and ATPase activity []. Importantly, the conformation of myosin, measured by its viscosity, was shown to reversibly change upon addition of ATP, which suggested “ for the first time ” that myosin was a “ contractible enzyme ” []. In the following years, it became apparent that one of the previously described forms of myosin, “Myosin B”, was likely a complex of actin and myosin, which physically interact to yield actomyosin [] (Fig.…”
Section: Interactions Give Structure and Regulate Enzymesmentioning
confidence: 99%
“…C The physical properties of myosin threads (Engelhardt, Lyubimova & Meitina, 1941) and of myosin in solution (Needham, Shen, Needham & Lawrence, 1941;Dainty et al 1944) are drastically altered when ATP is present. D KUhne's 'myosin' can be separated into two proteins, 'actin', and what is now known as myosin (F. B. Straub, 1943).…”
Section: The Mechanism Of Contractionmentioning
confidence: 99%